2004
DOI: 10.1021/jp030803j
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Studies (MCLH Simulations) of the CO−NO Reaction on Disordered Substrates and Their Relation with Experiments

Abstract: A Monte Carlo study is made of the reduction reaction of NO by CO over a uniform surface and on disordered substrates, some of them fractals, assuming a Langmuir−Hinshelwood mechanism and using experimental kinetics parameters proposed in the literature in the case of Rh as the catalyst. There is good agreement in the pressure and temperature intervals studied between the simulations and the analytic solutions of the mechanism for a uniform substrate. For nonuniform surfaces, in which the kinetics mechanism ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The Rh nanoparticles were very active, had a moderate decrease in activity at elevated pressures of NO, and did not undergo significant deactivation. These results are consistent with previous studies on Rh catalysts in this reaction, which found that supported Rh nanoparticles show decreased activity with increased NO pressure at 538 K [32] and that Rh shows very little deactivation for this reaction [33]. The Pd nanoparticles, however, were significantly less active in all conditions and deactivated at elevated pressure of NO.…”
Section: Discussionsupporting
confidence: 92%
“…The Rh nanoparticles were very active, had a moderate decrease in activity at elevated pressures of NO, and did not undergo significant deactivation. These results are consistent with previous studies on Rh catalysts in this reaction, which found that supported Rh nanoparticles show decreased activity with increased NO pressure at 538 K [32] and that Rh shows very little deactivation for this reaction [33]. The Pd nanoparticles, however, were significantly less active in all conditions and deactivated at elevated pressure of NO.…”
Section: Discussionsupporting
confidence: 92%
“…Fortunately, as shown in Appendix A, analytic solutions can be found for the covering using the approximation that assumes an equilibrium between the adsorbed species CO(a) and NO(a) and their molecules in the gas phase. This approximation, which we have used before [14,21,26] and which assumes high adsorption and desorption rates, is reasonable within the working range of the paper, as has been commented in the literature for the CO-NO [12] reaction. The validity of the approximation has also been confirmed in one of our previous works using Monte Carlo simulations [21] and by numerical integration of the mass balance equations [14].…”
Section: + ⎯→ ⎯ +mentioning
confidence: 58%
“…This approximation, which we have used before [14,21,26] and which assumes high adsorption and desorption rates, is reasonable within the working range of the paper, as has been commented in the literature for the CO-NO [12] reaction. The validity of the approximation has also been confirmed in one of our previous works using Monte Carlo simulations [21] and by numerical integration of the mass balance equations [14]. In that work it was found an excellent agreement between the analytical approximation, Appendix A, and the numerical solution.…”
Section: + ⎯→ ⎯ +mentioning
confidence: 58%
See 2 more Smart Citations